AN ASSESSMENTS OF MITIGATION OPTIONS IN THAI FORESTRY SECTOR FOR REDUCING CARBON EMISSIONS - Tantasirin, Chatchai; Tangtham, Nipon (วารสารวนศาสตร์ไทย, 2022)
Six mitigation options through six different management scenarios were assessed in terms of their effectiveness in reducing carbon emissions. They were analysed in terms of various alternative options; current trend scenario, based on current forest policies in operation, and two scenarios put forward in the Thai Forestry Sector Master Plan which are Master Plan Scenario and Self Sufficient Scenario. Three further scenario were considered combining the governments 5 Million Rai Plantation Project with the Current Trend Scenario, Master Plan Scenario and with the Self Sufficient Scenario. The Modified Comprehensive Mitigation Assessment Process (M-COMAP) was employed in this study to analyse trends in land-use change, carbon pool and sequestration, total costs and benefits of forest protection and reforestation programmes and their cost effectiveness indicators. The Current Trend Scenario was used as a baseline scenario, and analysis of the other five management scenario was compared to this baseline. Results indicate that the Self Sufficient Scenario with 5 Million Rai reforestation project provides the most favourable scenario for mitigation of carbon emission and the medium rotation reforestation of Self Sufficient Scenario shows to be the most suitable mitigation option among all options.